PENGARUH MARINASI JAHE MERAH (Zingiber officinale Rosc.) TERHADAP PERUBAHAN KADAR MINERAL ESENSIAL PADA DAGING SAPI KERING - Bambang Dwiloka; Shaquilla Aizza Widyasari Putri; Nur wantoro (Universitas Muhammadiyah Semarang, 2023)
Indonesian people's beef consumption will increase every year in line with population growth and increasing public awareness of the availability of protein sources. Therefore, it is necessary to preserve in the form of drying as an effort to support increased beef consumption through making dried beef. Making dried beef uses a red ginger blend whose success is influenced by the amount of concentration used. This study aims to determine the effect and best concentration of using a red ginger blend as an ingredient in marinating dried beef brisket on essential mineral levels. The experimental design used in this research was a completely randomized design with five treatments, but no repetition was carried out. Treatments were differentiated according to the concentration of red ginger blend used, namely P0=0%, P1=5%, P2=10%, P3=15%, and P4=20%. The data analysis used is that the test results are displayed in the form of a histogram and explained descriptively. The results of the research showed that treatment without smearing the ginger blend and smearing the red ginger blend with the concentration according to the treatment gave different results. The red ginger blend smearing can increase the levels of essential minerals in dried beef.